Determinants of Unintended Pregnancy in Central Java in 2022 - Ardiningsih, Eka Setya; Agushybana, Farid; Shaluhiyah, Zahroh (Universitas Airlangga, 2024)
Background: Unintended pregnancy presents major challenges to maternal and child health. Despite extensive family planning initiatives in Indonesia, particularly in Central Java Province, the reduction in unintended pregnancies remains limited, from 13.5% in 2017 to 11.3% in 2022. A thorough comprehension of the issue based on target characteristics is essential for crafting effective targeted programs. Aims: This study aims to analyze the determinants of unintended pregnancy among women of childbearing age in Central Java Province. Methods: This study is non-reaction research utilizing secondary data analysis from the 2022 Family Data Update in Central Java Province. The research focuses on women of childbearing age (15-49 years) who are currently pregnant. Result: The prevalence of unintended pregnancies among women of childbearing age in Central Java Province is 11.3%. There is a significant association between age at first marriage (p=0.000), desired number of children (p=0.000), employment status (p=0.000), health insurance enrollment (p=0.000), contraceptive use in the last 12 months (p=0.000), maternal age (p=0.000), and education level (p=0.000) with unintended pregnancies. Women of childbearing age who marry before the age of 21, desire more than 2 children, are unemployed, enrolled in health insurance, have used contraception in the last 12 months, and aged over 35 are more likely to experience unintended pregnancies. Conclusion: The determinants of unintended pregnancies among women of childbearing age in Central Java Province include the age at first marriage, the desired number of children, employment status, health insurance enrollment, contraceptive use in the last 12 months, and maternal age.